Key Push and Pull Factors Affecting Return to Work Identified by Patients With Long-Term Pain and General Practitioners in Sweden. (September 2019) - Lundberg, Tove; Melander, Stina
Research shows that working is positive for people with long-term pain but that work-related support from health professionals is inadequate. One explanation for this inadequacy is that patients and providers differ in terms of perspectives on motivation to work. In this article, we compare factors that 31 patients and 15 general practitioners consider important to promote return to work for people with long-term pain. We analyzed the interviews with thematic analysis and a motivational push and pull framework to cover different motivational factors, societal and individual, that might push or pull patients from or toward work. Providers said that a difference between working and nonworking patients is their level of individual motivation, while the patients' stories showed that the main difference was the physical (non)ability to push themselves to work. We suggest that work-related support can be improved by addressing such differences in clinical practice.